Stochastic differential equations of charged particle motion in toroidal plasmas - Gurin, A.A.; Yavorskij, V.O. (Вопросы атомной науки и техники, 2017)
Stochastic equations of charged particle motion in toroidal plasma are derived using the Ito theory of stochastic processes. Expressions for stochastic differentials of the full set of drift variables associated with the kinetic theory of charged particles in plasma with Coulomb collisions are obtained. Equations obtained may be used for the modelling of fast charged particle motion in toroidal plasmas, namely for Monte-Carlo simulation the dynamics of charged fusion products and beam ions in tokamaks. В терминах теории стохастических процессов Ито получены выражения для стохастических дифференциалов полного набора дрейфовых переменных, соответствующих кинетической теории заряженных частиц в плазме с кулоновскими столкновениями. Полученные стохастические уравнения движения являются последовательными с точки зрения учёта эффектов кулоновских столкновений и не являются более сложными по сравнению с теми, что обычно используются в традиционных модельных подходах. В термінах теорії стохастичних процесів Іто отримано вирази для стохастичних диференціалів повного набору дрейфових змінних, що відповідають кінетичній теорії заряджених частинок у плазмі з кулонівськими зіткненнями. Отримані стохастичні рівняння руху є послідовними щодо врахування ефектів кулонівських зіткнень, та не є складнішими у порівнянні із тими, що використовуються зазвичай в поширених модельних підходах.